RENCANA TEKNIS REKLAMASI TAHAP OPERASI PRODUKSI DAN NILAI EKONOMI PADA PERENCANAAN TAMBANG BATU ANDESIT DI DESA SIDOMULYO, KEC. PENGASIH, KAB. KULON PROGO, D.I. YOGYAKARTA - Putera, Muhammad Arifian Dharma; Lusantono, Oktarian Wisnu; Primaniyarta, Fernanda; Faa’iz, Firman Agna Nur (Jurnal Administrative Reform, 2025)
This study focuses on the reclamation planning for an andesite mining site in Sidomulyo Village, Kulon Progo, Yogyakarta. Using the Quarry Sidehill method, the project spans 21.5 hectares of mining land with a six-year operational period (2025–2030). Reclamation activities include land arrangement, topsoil spreading, drainage, and revegetation with sengon and teak trees, as well as kalopo plants for cover crops. The total reclamation cost is estimated at IDR 2.113 billion, comprising land management and revegetation costs. This plan aims to restore land functionality and promote sustainable environmental stewardship while supporting government and industry initiatives.